Quantitative And Qualitative Characteristics Of Male Bali Cattle In Kabila Bone Sub District - Abdul Malik Kamaru; Nibras Karnain Laya; Safriyanto Dako (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2026)
Purpose: This study aims to identify the quantitative and qualitative characteristics of Bali bull cattle in Kabila Bone District and provide foundational information for developing local superior breeding stock. Methodology: The study involved 20 Bali bull cattle aged 2–8 years. Quantitative data were obtained through morphometric measurements (body length, chest girth, body height, hip width, etc.), while qualitative traits were visually observed (coat color, leg markings, dorsal stripe, horns, and tail color). Data were analyzed descriptively by calculating mean, minimum, maximum, and standard deviation values. Results: The average body length was 101.00 cm, chest girth 148.45 cm, and body height 110.55 cm. The dominant coat color was black mixed with brown (45%), leg markings were mostly clearly defined (55%), dorsal stripes were mostly moderate (70%), all cattle had horns (100%), and black tail color dominated (85%). Findings: The Bali bulls in the study location exhibited characteristics consistent with pure Bali cattle, with minor variations due to environmental influences. Novelty: This study provides a comprehensive morphological documentation of Bali cattle in eastern Gorontalo, which has been rarely reported. Originality: It simultaneously describes both qualitative and quantitative traits of a local Bali cattle population that has not been previously documented. Conclusion: The Bali bull population in Kabila Bone District retains the original phenotypic characteristics and has strong potential to be developed as a superior breeding stock. Type of Paper: Research article.